2023
DOI: 10.58777/rbm.v1i1.19
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Workload and Career Development on Turnover Intention through Job Satisfaction as Variable Mediator

Abstract: This study aims to determine the effect of Workload and Career Development on Turnover Intention through Job Satisfaction as a Variable Mediator. The population used in this study were employees of PT Taiyo Sinar Raya Teknik with a total sample of 84 respondents. The sampling technique used was non-probability sampling with a purposive sampling technique using questionnaires distributed to respondents. Data analysis was carried out using SmartPLS 3. This study shows that workload has a positive and significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 12 publications
0
0
0
Order By: Relevance
“…This finding demonstrates that career development has a favorable but minor impact on turnover intention in Jakarta startup enterprises via job satisfaction. This finding is consistent with Dewi and Iqbal's (2023), Jayasri and Annisa's (2023), Kasdorf andKayaalp's (2020), andFitriani andLo's (2020) research. In evaluating this hypothesis, it is also possible to conclude that the career development hypothesis has no effect on turnover intention, hence the hypothesis is rejected.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…This finding demonstrates that career development has a favorable but minor impact on turnover intention in Jakarta startup enterprises via job satisfaction. This finding is consistent with Dewi and Iqbal's (2023), Jayasri and Annisa's (2023), Kasdorf andKayaalp's (2020), andFitriani andLo's (2020) research. In evaluating this hypothesis, it is also possible to conclude that the career development hypothesis has no effect on turnover intention, hence the hypothesis is rejected.…”
Section: Discussionsupporting
confidence: 90%
“…The Effect of Career Development on Turnover Intention According to Kasdorf and Kayaal (2020), there is a negative and significant influence between career development and turnover intention, where high career development in a company will significantly reduce the turnover intention rate in the company. This is also supported by Jayasri and Annisa (2023), whose research found that Career development has a negative and significant influence on turnover intention, where the more career opportunities open to employees in the company, the higher the turnover intention rate. Dewi and Nurhayati (2021) back up this claim by performing research on the effect of career development on turnover intention, which yields the same results: the lower the chance for employees to advance in their careers, the higher the turnover intention drive.…”
Section: Turnover Intentionmentioning
confidence: 63%
See 2 more Smart Citations